Sukhi Gift Box Enterprise / Alif Amaluddin ...[et al.] - Alif, Amaluddin; Jaimy Azdean, Nur Nadjmi Armiesha; Mohd Shah, Nora Alyanie; Mohd Zainol, Amiratul Aqilah; Saiful Effendy, Nur Fatihah (2022)
Sukhi Gift Box Enterprise is a business that offers a variety of gift box and bouquet designs for Malaysians. People nowadays love surprises and present. Based on that statement, our company will serve the best surprise and present service that can be customized by customers where it is good to satisfy their desires. Therefore, our company has chosen to take this advantage to introduce a giftbox and bouquet service to Malaysians. Sukhi Gift Box is a partnership-based business formed by five partners consisting of two male employees and three female employees. However, each of the partners will play various positions in the company’s management, including General Manager, Administration Manager, Marketing Manager, Operational Manager, and Finance Manager. The mission of Sukhi Gift Box is to bring joy, comfort and inspiration into the lives of customers by providing high quality but affordable gift boxes. On top of that, our vision is to become one of the best Gift Box Companies in the local area.